Cost of Capital - challenges for companies in current economic environment - Carl Heinz Daube (ZBW - Leibniz Information Centre for Economics, 2023)
In July 2022, the ECB started to gradually increase the key interest rate in order to bring the increased inflation back into the target corridor. An increase in the cost of capital for countries and companies could be observed much earlier. This increase of cost was more significantly caused by the fact that the social and economic conditions in Germany and Europe have changed considerably in recent years. This working paper examines selected conditions regarding their impact on the cost of capital for companies. – – Im Juli 2022 hat die EZB angefangen, den Leitzins schrittweise zu erhöhen, um so die gestiegene Inflation wieder in den Zielkorridor zuführen. Ein Anstieg der Kapitalkosten für Staaten und Unternehmen war schon deutlich früher zu beobachten. Maßgeblich verursacht wurde dieser Anstieg dadurch, dass sich die gesellschaftlichen und wirtschaftlichen Rahmenbedingungen in Deutschland und Europa in den letzten Jahren stark verändert haben. In diesem Working Paper werden ausgewählte Rahmenbedingungen hinsichtlich ihrer Wirkung auf die Kapitalkosten von Unternehmen untersucht.
Keywords: G10; 330; cost of capital; weighted average cost of capital; inflation; interest rates